Classical Models for Twin Data. Issue 1 (2nd January 2021) - Jöreskog, Karl G.
ABSTRACT: The classical models ACE and ADE were used in the 1990s to estimate heredity of a phenotype from data on monozygotic and dizygotic twins. These models are extended to a model called ACDE with four parameters instead of only three. It is showed how these models can be easily estimated by maximum likelihood. The models and methods are extended to two populations in which the heredity is the same in both populations. Examples are given to estimate the heredity of BMI using twin data from the UK and Australia.